The role of affect-communication and rule setting in perceived family support and school adjustment (European Journal of Education and Psychology, 2019)
Previous research suggests that parental socialization styles affect the implementation of family support strategies and are related to school adjustment. Nevertheless, the precise nature of the influence of socialization practices on these variables during adolescence has yet to be determined. The aim of this study was therefore to examine (separately) the direct influence of maternal and paternal affectcommunication and rule setting on adolescent participants' perceived family support, and to analyze the relationship between these dimensions and school adjustment. The sample comprised 1190 secondary school and Spanish Baccalaureate students (47.1% boys and 52.3% girls; Mage = 14.76 years, SD = 1.55) from the Autonomous Community of the Basque Country. The Affect Scale (EA-H) and the Rules and Demands Scale (ENE-H) were used to assess parental socialization practices, and the subscale for perceived family support from the Social Support from Family and Friends (AFA-R) measure and the School Engagement Measure (SEM) were used to assess school engagement, with the mean grades earned by participants being taken as a measure of academic performance. The results obtained reveal that paternal affect-communication contributes more than maternal affect-communication to adolescents' perception of having family support, whereas in relation to rules, only maternal rule setting was found to have an effect on perceived family support, with this effect being negative. Both components of parenting styles were found to be linked to school engagement. In the final sections, the data are discussed and the study's limitations presented.